Effect of tree trash incorporation from different arboreal species on co2, ph and phosphorus in a vitric haplustand soil - Morán, Yuri; Portillo, Maritza; Burbano O., Hernán; Vélez L., Jorge; Ruiz E., Hugo; Navia E., Jorge (Revista de Ciencias Agrícolas, 2013)
This research was carried out using plant material from established arboreal plantations in the FEDEPAPA experimental farm, located in Obonuco, municipality of Pasto, a dry forest low montano zone life and a Vitric Haplustand soil.The effect of incorporation of tree trashes of four species on CO2 content levels, pH and P availability was evaluated under laboratory conditions. Soil samples were collected from areas with grass cover and plant material from silvo pastoral systems of acacia (Acacia decurrens), aliso (Alnus acuminata), eucalipto (Eucalyptus globulus) and quillotocto (Tecoma stans) all of them associated with kikuyo grass (Pennisetum clandestinum) and brought to the laboratory; the material was dried both in oven and outdoors during three days. For the sutdy it was used a split plot arrangement in a completely randomized block design with four blocks, where the treatments were 4 with trash from the four tree species and one without trash and two levels of trash, 2 t.ha-1 and 1 t.ha-1 The experiment was conducted for 16 weeks, with soil maintained at field capacity. According to results highly significant differences for treatments respect to content of CO2 and P; significant for levels of tree trash and highly significant for the interaction sepecies x levels; the use of quillotocto trash caused the highest change of the P available concentration (41,99 mg/kg) and of pH(6,6). The highest values of CO2 were obtained with aliso, that showed a C:N ratio of 20,5.